2014
DOI: 10.4161/21645515.2014.980210
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus specific dual HLA binding T cell epitopes induce CD8+T cell responses in seropositive individuals

Abstract: Dengue virus infects an estimated 300 million people each year and even more are at risk of becoming infected as the virus continues to spread into new areas. Despite the increase in viral prevalence, no anti-viral medications or vaccines are approved for treating or preventing infection. CD8C T cell responses play a major role in viral clearance. Therefore, effective vaccines that induce a broad, multi-functional T cell response with substantial cross-reactivity between all virus serotypes can have major impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Our previous studies demonstrated that DV specific free peptides can activate CD8CT cells in vitro. 28,29 Here, we evaluated if the same peptides formulated with nanoparticles could enhance DV specific T cell response. A total of 6 HLA-A2 C , A2 C /A24 C dual binding DV peptides (Table 1) were selected and formulated in 0.3% CaPNP particle suspension either individually or combined as a pool of multiple peptides.…”
Section: Specific Capnp/multipeptide Vaccine Formulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies demonstrated that DV specific free peptides can activate CD8CT cells in vitro. 28,29 Here, we evaluated if the same peptides formulated with nanoparticles could enhance DV specific T cell response. A total of 6 HLA-A2 C , A2 C /A24 C dual binding DV peptides (Table 1) were selected and formulated in 0.3% CaPNP particle suspension either individually or combined as a pool of multiple peptides.…”
Section: Specific Capnp/multipeptide Vaccine Formulationmentioning
confidence: 99%
“…Dengue virus specific MHC class I associated peptides identified previously by immunoproteomics. 28,29 Peptide…”
Section: Specific Capnp/multipeptide Vaccine Formulationmentioning
confidence: 99%
See 3 more Smart Citations